2017
DOI: 10.3201/eid2312.170532
|View full text |Cite
|
Sign up to set email alerts
|

Bourbon Virus in Field-Collected Ticks, Missouri, USA

Abstract: Bourbon virus (BRBV) was first isolated in 2014 from a resident of Bourbon County, Kansas, USA, who died of the infection. In 2015, an ill Payne County, Oklahoma, resident tested positive for antibodies to BRBV, before fully recovering. We retrospectively tested for BRBV in 39,096 ticks from northwestern Missouri, located 240 km from Bourbon County, Kansas. We detected BRBV in 3 pools of Amblyomma americanum (L.) ticks: 1 pool of male adults and 2 pools of nymphs. Detection of BRBV in A. americanum, a species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
108
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 19 publications
4
108
0
3
Order By: Relevance
“…BRBV replicates in cell lines derived from the hard ticks Amblyomma, Hyalomma and Rhipicephalus . Together with the geographic location of the BRBV infection and the geographic distribution of a number of Amblyomma americanum ticks (Savage, et al, 2017;Savage, et al, 2018), these studies strongly suggest that the lone star tick is a vector of BRBV transmission to humans.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…BRBV replicates in cell lines derived from the hard ticks Amblyomma, Hyalomma and Rhipicephalus . Together with the geographic location of the BRBV infection and the geographic distribution of a number of Amblyomma americanum ticks (Savage, et al, 2017;Savage, et al, 2018), these studies strongly suggest that the lone star tick is a vector of BRBV transmission to humans.…”
Section: Introductionmentioning
confidence: 82%
“…Later, two additional cases of BRBV infection have been reported. In 2015, a patient from Payne County, Oklahoma, USA tested positive for neutralization antibodies to BRBV before fully recovering (Savage, et al, 2017). In June 2017, a 58-year-old woman from Missouri died from an infection of BRBV after she had been misdiagnosed for a significant period of time (Bricker, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later findings included leukopenia, thrombocytopenia, hyponatremia, and mild transaminitis; the case patient then developed congestive heart failure and later died after withdrawal of care [27]. A study of tick populations in Missouri revealed that Amblyomma americanum ticks were carriers of the virus, though transmission from these ticks is not certain [28].…”
Section: Heartland and Bourbon Virusesmentioning
confidence: 99%